Análise da eficiência do gerenciamento de resíduos sólidos de saúde no Hospital Universitário João de Barros Barreto - SOUZA, Rafael Monteiro de (Universidade Federal do Pará, 2018)
Study of the management of Solid Waste of Health Services - RSS at the University Hospital João de Barros Barreto - HUJBB, analyzing and mapping the management processes of RSS from its generation to the final delivery to the collecting company. For this, the impact of the sector on the Hospital's operating expenses was evaluated and, then, actions were proposed to improve the management, transportation and destination processes of the RSS in the HUJBB. The methodology used in the study was applied research, of a descriptive-exploratory nature, using methods of documentary survey in the institution, interviews with the people involved and systematic observation with field research in the sectors. As a result of the qualitative-quantitative research, it was verified that in the year 2016 55,878.05 Kg of RSS were generated, which resulted in an annual expense of R $ 134,588.06 RSS in the HUJBB. The research was verified that the management of the RSS is inefficient, and the deficiency in the operational management reduces the commitment of the employees involved in the process, reason for the need to improve the infrastructure and reformulate the procedures in the solid waste sector of HUJBB.